PERAN BRAND AUTHENTICITY DAN SOCIAL MEDIA MARKETING ACTIVITIES (SMMA) DALAM MENDORONG BRAND TRUST, BRAND AFFECT DAN BRAND LOYALTY: UNCLE Z KOPITIAM SENOPATI JAKARTA - Alghifari, Nandito; Rofianto , Whony; Wulandari , Nuri; Pracoyo , Antyo (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to examine the influence of Brand Authenticity and Social Media Marketing Activities (SMMA) on Brand Trust and Brand Affect in shaping Brand Loyalty, with Uncle Z Kopitiam Senopati Jakarta as the research object. The exogenous variables in this study are Brand Authenticity and Social Media Marketing Activities, while the endogenous variables are Brand Trust, Brand Affect, and Brand Loyalty. The research hypothesis testing was conducted using Partial Least Squares (PLS) with SmartPLS 4 software. Data collection was carried out using a Google Form questionnaire to gather the required information. The sample for this study consisted of 70 people who have visited Uncle Z Kopitiam Senopati Jakarta. The analysis results show that Quality Commitment (QC) has a positive effect on Brand Reliability (BR), Quality Commitment (QC) has a positive effect on Brand Intention (BI), Sincerity (SIN) does not affect Brand Reliability (BR), Sincerity (SIN) does not affect Brand Intention (BI), Heritage (HE) does not affect Brand Reliability (BR), Heritage (HE) does not affect Brand Intention (BI), Brand Reliability (BR) positively affects Brand Affect (BA), Brand Reliability (BR) does not affect Brand Loyalty (BL), Brand Intention (BI) does not affect Brand Affect (BA), Brand Intention (BI) positively affects Brand Loyalty (BL), Brand Affect (BA) does not affect Brand Loyalty (BL), Social Media Marketing Activities (SMMA) positively affect Brand Reliability (BR), and Social Media Marketing Activities (SMMA) do not positively affect Brand Intention (BI).